PERBANDINGAN KINERJA KEUANGAN BANK DEVISA DAN BANK NON DEVISA DI INDONESIA - Sulistyowati, 09.05.52.0128; Suwarti, Titiek (Students Journal of Accounting and Banking, 2013)
Aim in this watchfulness compares foreign exchange bank finance performance and bank non foreign exchange in indonesia. data memabil financial statement from year 2009-2011 shaped balance and balance report. this secondary data is got direct from indonesia bank to cultivated and look for to know how big value car, npl, roa, roe, bopo,Â and ldr from every bank. Taking technique sapel done by purpossive sampling from 65 foreign exchange banks and bank non foreign exchange is got 35 foreign exchange banks and bank non foreign exchange that is 23 foreign exchange banks and 12 banks non foreign exchange. tool to test hypothesis in this watchfulness skweness, independent t-test,Â and mann whitney test. Analysis result uses method independent t-test and mann whitney got result not found ratio difference npl, roe, bopo and ldr between foreign exchange bank and bank non foreign exchange. on the contrary there difference between car and roa foreign exchange bank and basin non foreign exchange.Keywords: Foreign Exchange bank, bank non foreign exchange, CAR, NPL, ROA, ROE, BOPO, LDR.